HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DAN KOORDINASI MATA-TANGAN DENGAN KETERAMPILAN LAYUP SHOOT PADA TIM BASKET PUTERA SMAN 2 PEKANBARU - Mohd Fadlin; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak, this research was conducted to find out wheather there was correlationbetween explosive power of leg muscle and eye-hand coordination in lay-up shoot skillat male basketball team of SMA 2 Pekanbaru. So that in lay-up shoot skill they gotmaximum result. The design of this research was correlation research. The populationwas basketball team of SMA 2 Pekanbaru consisted of 15 players. The instruments inthis research were tes vertical jump, eye-hand coordination, lay-up shoot whichpurposed to measure height of jump, coordination and accuration. After that the datawere calculated by stastistic to test the normality with lilifor test on significant 0,05α.The hypothesis was there was correlation explosive power of leg muscle and eye-handcoordination in lay-up shoot skill at male basketball team of SMAN 2 Pekanbaru. Basedon lilifor analysis, it resulted Lcount (x1) in 0,196 and Ltable 0,220, Lcount (x2) in 0,200 danLtabel 0,220. So that the sample was from population with normal distribution. Fromproduct moment got Rcount 0,843 and Rtable 0,532. Ho was accepted and Ha wasrejected.Therefore there was correlation between explosive power of leg muscle andeye-hand coordination in lay-up shoot skill at male basketball team of SMAN 2Pekanbaru.Keyword: Explosive power,eye-hand coordination, lay-up shoot.